Groundwater flow underneath mound spring tufas from geophysical surveys in the southwestern Great Artesian Basin, Australia. Issue 7 (2nd October 2016) - Inverarity, K.; Heinson, G.; Hatch, M.
ABSTRACT: Artesian springs, which form carbonate mounds at the surface, occur in groups along the southwestern edge of the Great Artesian Basin (GAB), in northern South Australia. Their underground structure and relationship to faulting are not well understood. This study investigated four mound spring groups (Beresford Spring, Warburton Spring, the Bubbler Spring group, and Freeling Springs), which have different geological settings, using a range of geophysical techniques: self-potential (SP), magnetotellurics (MT) and time-domain electromagnetics (TEM). The results confirmed that despite generally similar mound morphologies at the surface, spring vents in different groups have different mechanisms for sourcing water from the GAB aquifer. SP measurements effectively showed where most of the vertical flow occurs at all groups, while MT and TEM models identified the location of faults, other geological structures and the thickness of the Bulldog Shale aquitard. Beresford and Warburton springs are similar in that the spring locations at both are directly related to points on a regional-scale fault, which appears to provide a low permeability pathway to the surface. At the Bubbler Springs group, a regionally aligned fault identified in MT data seems to be bounding an area where the aquifer is much closer to the surface (and the overlying aquitard has been thinned) where the spring abundance is highest. SP responses indicate that shallow flow paths feeding individual vents are unrelated to the fault. At Freeling Springs, the SP suggests that groundwater is flowing up within shallow aquifers, and that spring location is offset from this upward flow, instead located on range-front faults that provide the final conduit to the surface.